Wagner, Kasper Holten Wagners Rhinguld i vridemaskinen: Et eksperiment med Kasper Holten - Parly, Nila (Peripeti, 2021)
Nila Parly diskuterer et kreativt forskningsseminar, hvor instruktøren Kasper Holten, en gruppe forskere og studerende fra nordiske universiteter og et sangerhold fra Operaakademiet eksperimenterede med at visualisere Wagners musik fra sidste scene af Rhinguldet med udgangspunkt i en dramaturgisk skitse skrevet specielt til lejligheden af den amerikanske poststrukturalist Carolyn Abbate. Parly analyserer processen ud fra en teoretisk vinkel med rødder i performance studies. This article discusses a creative research seminar, during which Danish opera director Kasper Holten, a group of scholars and students from universities in the Nordic countries, and a team of young singers experimented with stagings of the last scene of Wagner’s Rheingold on the basis of a dramaturgical sketch written specifically for this purpose by the American post-structuralist Carolyn Abbate. In the course of the article the process is analysed from a theoretical viewpoint founded in performance studies, and the ideas are developed further in a hypothetical production inspired by ilm director Lars von Trier’s thoughts on “enriched darkness”.